Edukasi Penerapan Higiene dan Sanitasi Rumah Makan di Minahasa Utara - Florianus Hans Matheus Mawo; Odi Roni Pinotoan; Lady Galatia Lapian; Firmita Dwiseli (Jurnal Medika: Medika, 2026)
Restaurant sanitation is a crucial aspect in preventing foodborne diseases, including contamination by Escherichia coli, which commonly occurs due to poor hygiene practices, improper dishwashing procedures, and inadequate sanitation facilities. This Community Service Program (PKM) aimed to provide education on hygiene and restaurant sanitation as well as monitor the presence of E. coli on eating utensils in North Minahasa. The methods employed included educational sessions, observations, and summative evaluations of food handlers’ behaviors and sanitation facilities. The results showed low consistency in the use of personal protective equipment, limited availability of standard handwashing facilities, and the presence of E. coli on several eating utensils. Although all participants stated that the educational materials were beneficial, only 60% expressed commitment to applying the newly acquired practices. Nevertheless, all participants (100%) requested continued assistance, indicating the need for further interventions to bridge the gap between knowledge and actual practice. These findings emphasize that a single educational session is insufficient; continuous mentoring, monitoring, and technical guidance are required to improve sanitation standards in restaurants and support food safety within small and medium-sized food enterprises